RISE OF CHINA: GLOBAL ORDER AND THE REGION - Prof. Dr. Iram Khalid, Prof. Dr. Muhammad Iqabl Chawla (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The changing world order has given rise to the debate on the emergence of China. Currently, China has become the future of 21st century, weather it would lead to possibility of stability or chaos. The main point of this research weather US will ignore the changing world order without alteration and to confront to rise of China or it will recognize inevitability of alteration then the new world order based on distribution and balance of power. Thus the future of world would represent a multipolar stability in which each player holds the sphere of influence which iscommensurate to its real power.